A Study Of Al-Ghazali’s Concept Of Moral Behavior Among Postgraduate Students - Alshbaili, Omar Alamari M. (2013)
The purpose of the current study was to understand and identify the moral behavior based on Al-Ghazali writings. Also to clarify foundational, characteristics, standard moral behavior, and knowing the ways that lead to the acquisition of good morals as a motivator in developing the different aspects of human personality. Both qualitative and quantitative research methodology was utilized in the current study. In the qualitative research methodology the texts were identified, gathered, categorized, and extracted with relation to the concepts, and thoughts abstracted from the books written by Al-Ghazali. In addition, the current study contained a questionnaire to understand and identify the moral behavior among university student. The population of the current study consisted 241 postgraduate students (Master and PhD) from the school of Education Studies and the school of Social Sciences of the University Science Malaysia. The results revealed that the level of understanding was very great and the arithmetic mean in general amounted 4.29. Also, there is no statistical differences existed based on gender. There are great amount of useful educational and psychological information in Al-Ghazali’s the writings specifically those related the concept of moral behavior as a comprehensive and effective concept in development the human psychological aspects from both mind and religious law. Besides, clarifies the right path to moral behavior and feeds many of the basic qualities which provide the basis of good morals.